2006
DOI: 10.1212/01.wnl.0000238164.90657.c2
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Activity Log-28

Abstract: The participant Motor Activity Log is reliable and valid in individuals with subacute stroke. It might be employed to assess the real-world effects of upper extremity neurorehabilitation and detect deficits in spontaneous use of the hemiparetic arm in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
330
1
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(348 citation statements)
references
References 22 publications
2
330
1
15
Order By: Relevance
“…Most of the studies included only reported UE impairment outcome measures. Apart from the Motor Activity Log, the selected outcome measures do not specifically assess UE activities of daily living (Uswatte et al, 2006). In addition, including outcome measures such as the Stroke Impact Scale in clinical trials of tDCS plus rehabilitation (Duncan et al, 2003) would give an insight into the effect of intervention on participants' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies included only reported UE impairment outcome measures. Apart from the Motor Activity Log, the selected outcome measures do not specifically assess UE activities of daily living (Uswatte et al, 2006). In addition, including outcome measures such as the Stroke Impact Scale in clinical trials of tDCS plus rehabilitation (Duncan et al, 2003) would give an insight into the effect of intervention on participants' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome measures were: (1) Action Research Arm Test (ARAT), an UL functional measure which involves testing the ability to grasp, move, and release objects differing in size, weight, and shape by the affected UL (Lyle, 1981), (2) Motor Activity Log-28 (MAL), a semi-structured interview during which respondents rate how well (quality of movement scale) they use the paretic hand during 28 UL activities of daily living (Uswatte, Taub, Morris, Light, & Thompson, 2006) and (3) Stroke Impact Scale (3.0) (SIS) which evaluates function and quality of life in eight clinically relevant domains on the basis of self-report (Duncan, Bode, Min Lai, & Perera, 2003).…”
Section: Assessment and Outcome Measuresmentioning
confidence: 99%
“…In this study, we were particularly interested in measuring the activity of the upper limbs. Uswatte et al provided significant evidence about the validity and reliability of accelerometry to measure upper-limb activity in stroke [4][5][6][7][8]. Details about the clinometric properties of upper-limb accelerometrybased measurements are published elsewhere [3].…”
Section: Introductionmentioning
confidence: 99%